3114 Investigating the therapeutic potential of parthenolide in the treatment of hematopoietic neoplasms in dogs. (27th March 2019) - Schlein, Lisa J; Peterson, Aubree; Rose, Barbara; Thamm, Douglas
Abstract : OBJECTIVES/SPECIFIC AIMS: Determine PTL's mechanism(s) of action in a panel of canine hematopoietic cell lines; this will enable us to 1) verify that PTL is working as expected and 2) rationally select combination therapeutics. Characterize the in vitro sensitivity of canine hematopoietic cell lines to PTL in combination with other chemotherapeutic agents. Determine immunohistochemical NFκB expression in tissue microarrays of spontaneous canine neoplasms and correlate with outcome-linked data. Characterize the in vivo sensitivity of canine hematopoietic cell lines to PTL using a murine xenograft model. METHODS/STUDY POPULATION: Growth inhibition assays were performed using a panel of canine mast cell, histiocytic sarcoma, lymphoma, and leukemia cell lines, with PTL alone or in combination with redox-perturbing standard-of-care therapeutics. Cell death was assessed using flow cytometry. Immunofluorescence and immunoblotting were used to assess NFκB localization and phosphorylation of NFκB p65 (transcriptional activation), respectively. Intracellular glutathione with and without PTL and combination chemotherapeutics will be assessed spectrophotometrically. Archived spontaneous canine tumors will be evaluated immunohistochemically (IHC) for increased NFκB pathway activation relative to normal control tissues. Nude mice will receive intravenous, intraperitoneal, or subcutaneous injections of canine HS cells and will be treated with PTL or with PTL in combination with standard-of-care chemotherapeutics. RESULTS/ANTICIPATED RESULTS: Results: All immortalized canine cell lines evaluated are sensitive to PTL therapy and undergo dose-dependent apoptosis following exposure to drug. PTL exposure leads to inhibition of NFκB, as evidenced by immunofluorescent nuclear exclusion and decreased p65 phosphorylation. Some chemotherapeutics appear to synergize with PTL in vitro. Anticipated results: We expect to find increased IHC NFκB pathway activation in malignantly transformed tissues relative to controls. We expect standard-of-care therapeutics to synergize with PTL in vivo based on preliminary in vitro data. DISCUSSION/SIGNIFICANCE OF IMPACT: These studies will determine whether PTL therapy may be beneficial in dogs with a variety of hematopoietic neoplasms, either alone or in combination with other therapeutics that are currently in clinical use. Dogs with mast cell or histiocytic neoplasia are an excellent model for rare and deadly human diseases, which may also benefit from PTL therapy.